2008
DOI: 10.1177/0193945907312975
|View full text |Cite
|
Sign up to set email alerts
|

Educators' Experience of Teaching Nursing Research to Undergraduates

Abstract: Most research pertaining to the teaching of nursing research has focused on learning outcomes and students' attitudes toward research. Few scholars have explored what it is like to teach nursing research. The purpose of this study was to describe the experience of teaching undergraduate nursing research. Data were obtained from 12 nurse educators through e-mail interviews and analyzed using Giorgi's method of descriptive phenomenology. Four meaning units describe the experience: marketing research content, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 28 publications
(31 reference statements)
1
8
0
Order By: Relevance
“…Although the majority of educator in this study reported high ability to perform these steps, others said that they have limited ability to do so. This has also been reported by other researchers [23,26] . This ability could be improved through adopting team approach in finding, discussing, analyzing and agreeing on evidence.…”
Section: Factors Influencing Adopting Evidence-based In Nursing Educasupporting
confidence: 91%
See 1 more Smart Citation
“…Although the majority of educator in this study reported high ability to perform these steps, others said that they have limited ability to do so. This has also been reported by other researchers [23,26] . This ability could be improved through adopting team approach in finding, discussing, analyzing and agreeing on evidence.…”
Section: Factors Influencing Adopting Evidence-based In Nursing Educasupporting
confidence: 91%
“…Many of the nurse educators are in fact prepared to be researchers and experts in their area of study. They, however, receive limited preparation to be educators [23] . Although education is their primary role once joining the faculty, there is still a limited focus on the required preparation to teach crucial concepts to contemporary nursing practice like evidence-based.…”
Section: Factors Influencing Adopting Evidence-based In Nursing Educamentioning
confidence: 99%
“…The culturally-based transactions and interactions that are crucial within the acculturation process also have not been elucidated. [42,43] There is a need to extend the evidence base for nursing education, [44] and a key element in doing so is the investigation of acculturation to RU and its related outcomes. Therefore, the following research question guided the study: "What is the enactment of acculturation in RU within a nursing education curriculumin-action?…”
Section: Literature Reviewmentioning
confidence: 99%
“…Strategies such as assigning research articles for reading, using textbooks that incorporate nursing research, or citing publications within our PowerPoint ® slides do little to impress on students the exciting and care-transforming nature of nursing research. Even courses specifically dedicated to evidence-based practice can fail to connect students to their faculty member's research in a meaningful way (Mansour & Porter, 2008). This is problematic because missing opportunities to make research relevant to BSN students can limit progress toward the ultimate goal of cultivating the next generation of consumers and implementers of nursing research.…”
mentioning
confidence: 99%